The Influence of Attitude, Subjective Norms, and Perceived Behavioural Control on Intention to Return to Work: A Case of SOCSO’s Insured Employees - Tan Fee Yean; Johanim Johari; Annis Fadilla Mohd Sukery (Kajian Malaysia, 2015)
Intention to return to work is based on employees' perception of the likelihood or the probability of going back to work after a prolonged illness caused by workrelated injuries or other illnesses. Based on the Theory of Planned Behaviour, this study proposes that employees' attitude, subjective norms, and perceived behavioural control will influence their intention to return to work. Data were gathered through a questionnaire administered to 160 SOCSO's insured persons, located all over Malaysia. Using the partial least squares (PLS) analysis method, we found that attitude and subjective norms have positively influenced intention to return to work among respondents. Perceived behavioural control however, has a non-significant impact on respondents' intention to return to work. The study offers plausible explanations for the results and discusses the theoretical and practical ramifications of the results.